Decisions of the Сongress of the Orthodox military clergy of the Southwestern front in Proskurov in 1917 - Starostenko, Eleonora V. (Journal of the Belarusian State University. History, 2022)
The decisions of the congresses of the military and naval clergy, held at the beginning of the 20th century, remain little studied to this day. Turning to this topic, researchers most often focus on the decisions of congresses of all-Russian significance which is the 1st All-Russian congress of the military and naval clergy (July 1914, Petrograd), less often on the decisions of the 2nd All-Russian congress of the military and naval clergy (July 1917, Mogilev). However, front-line congresses also played an important role in the history of the institute of military priests: they took place in the Southwestern (5–7 May 1917), Western (24–28 May 1917), Romanian (25 June 1917) and Northern (26–28 June 1917) fronts. This article discusses the work of the first of them which is the Сongress of the Orthodox military clergy of the Southwestern front in Proskurov in May 1917. The author of the article analyses the main decisions of this congress. The attitude of the military clergy of the front to the war, participation in the political parties, organisation of cultural and educational activities are shown. The proposals of the delegates on the reorganisation of the administration of the department and the introduction of an elective principle are analysed. It is shown whether the opinion of the participants of the congress in Proskurov coincided with the decisions of the 2nd All-Russian congress of the military and naval clergy in Mogilev. The article was prepared on the basis of archival documents and materials of the periodical press. In particular, documents from the funds of the Russian State Historical Archive (Saint Petersburg) such as protocols of the sessions of the Сongress of the Orthodox military clergy of the Southwestern front, the resolutions of the protopresbyter on the decisions of the congress, the protocols of the sessions of the 2nd All-Russian congress of the military and naval clergy were used.